2007
DOI: 10.1002/bit.21457
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide production from elemental sulfur by Desulfovibrio desulfuricans in an anaerobic bioreactor

Abstract: Feasibility of elemental sulfur reduction by Desulfovibrio desulfuricans in anaerobic conditions in a stirred reactor was studied. Hydrogen was used as energy source, whereas the carbonated species were bicarbonate and yeast extract. Attention was paid to reactor engineering aspects, biofilm formation on the sulfur surface, hydrogen sulfide formation rate and kinetics limitations of the sulfur reduction. D. desulfuricans formed stable biofilms on the sulfur surface. It was found that active sulfur surface avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…For instance, Guo et al (2021) reports VSPR reaching 0.844 ± 0.115 g S 2-•L -1 •d -1 at pH 3.8 and 25 °C while Sun et al (2020b) found VSPR up to 0.845 g S 2-•L -1 •d -1 at pH 3.5 and room temperature (not specified). Furthermore, the VSPR at the circumneutral pH is also in the same order of magnitude of those reported from research performed at laboratoryscale (Escobar et al, 2007;Zhang et al, 2018a) and industrial applications (Gonzalez-Contreras et al, 2016), under comparable pH and temperature conditions. This consistency in VSPR across studies, transcending differences in inoculum, electron donor, S 0 source, operational parameters, reactor configurations, and scale, hints at an intrinsic limit in microbial S 0 -reduction rates.…”
Section: Shifting Of the Microbial Community Upon Acidificationsupporting
confidence: 82%
“…For instance, Guo et al (2021) reports VSPR reaching 0.844 ± 0.115 g S 2-•L -1 •d -1 at pH 3.8 and 25 °C while Sun et al (2020b) found VSPR up to 0.845 g S 2-•L -1 •d -1 at pH 3.5 and room temperature (not specified). Furthermore, the VSPR at the circumneutral pH is also in the same order of magnitude of those reported from research performed at laboratoryscale (Escobar et al, 2007;Zhang et al, 2018a) and industrial applications (Gonzalez-Contreras et al, 2016), under comparable pH and temperature conditions. This consistency in VSPR across studies, transcending differences in inoculum, electron donor, S 0 source, operational parameters, reactor configurations, and scale, hints at an intrinsic limit in microbial S 0 -reduction rates.…”
Section: Shifting Of the Microbial Community Upon Acidificationsupporting
confidence: 82%
“…The presence of Desulfovibrio species with elemental sulfur as electron acceptor opens possibilities for further studies, as there are no reports of extended sulfidogenesis from the reduction of sulfur coupled to the degradation of complex organic matter by this group. Escobar et al (2007) showed the feasibility of elemental sulfur reduction by Desulfovibrio desulfuricans with hydrogen as electron donor and obtained maximal sulfide production rates of 2.1 g H 2 S L −1 d −1 . However, Biebl and Pfennig (1977) tested D. desulfuricans and D. vulgaris and no growth on elemental sulfur was observed, but slow and definite growth was observed for D. gigas.…”
Section: Electron Acceptor Screeningmentioning
confidence: 94%
“…The aquatic environmental pollution originating from heavy metals in solution is of utmost relevance due to its impact on public health, environment, and economy. Sulfidogenic reactors have become suitable alternatives for the treatment of metalrich wastewaters (Escobar et al, 2007;Gallegos-Garcia et al, 2009), with high levels of metals precipitated as highly insoluble metal sulfides. As a proof of concept, the stripping of sulfide for heavy metal precipitation shown in this study (Figure 6) increased the possibility of degrading the highly energetic bonds in LCFA compounds, mitigating the complexity of FOGs in lipid-rich wastewater while removing and recycling metals from metallurgical emissions.…”
Section: Metal Recoverymentioning
confidence: 99%
“…In an anaerobic stirred reactor, fed in batches, sulfur could be biologically reduced with Desulfovibrio desulfuricans, however, available surface area of the sulfur limited the rate of reaction (Escobar et al, 2007). (Dar, Stams et al, 2007).…”
Section: % Of the Total Bacteria In The Biofilm In Association Withmentioning
confidence: 99%